1994
DOI: 10.1007/bf00144120
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of iron accumulation in cardiac myocytes during the treatment of iron overload in gerbils with the hydroxypyridinone iron chelator CP94

Abstract: Gerbils administered iron dextran are the only animal species which have been shown to develop hemochromatosis of the liver and heart in the same manner as transfusion dependent homozygous thalassemics. The iron chelating hydroxypyridinone, CP94, has been administered prophylactically to iron overloaded gerbils in a dosing regime which favors the formation of bidentate chelated iron, to examine the possibility of additional toxicity being caused to the liver and heart by the bidentate chelated iron complex. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 14 publications
1
19
1
Order By: Relevance
“…Recent studies also suggested that iron and/or iron-mediated increase in the extent of oxidative stress play a role in the fibrotic changes not only in the liver 16,33 but also in other organs such as heart. 34,35 Our data may suggest the possibility that iron may also have a role in the vascular remodeling in vivo in certain diseased conditions, such as increased circulating Ang II.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies also suggested that iron and/or iron-mediated increase in the extent of oxidative stress play a role in the fibrotic changes not only in the liver 16,33 but also in other organs such as heart. 34,35 Our data may suggest the possibility that iron may also have a role in the vascular remodeling in vivo in certain diseased conditions, such as increased circulating Ang II.…”
Section: Discussionmentioning
confidence: 97%
“…20 A letter in response to these findings noted that when the same biopsy specimens were reviewed by another hepatopathologist in a masked manner but excluding specimens with insufficient numbers of portal tracts, no progression of liver fibrosis was found in the patients treated with deferiprone. 68 The description of increased rates of iron accumulation and hepatotoxicity in iron-loaded gerbils after treatment with dimethyl-3-hydroxypyrid-4-1 (CP94), 69 a compound closely related to deferiprone, 70,71 has been identified as evidence supportive of the hepatotoxicity and fibrogenic effect of deferiprone. 20,26 However, CP94 (dimethyl-3-hydroxypyrid-4-1) and deferiprone (dimethyl-3-hydroxypyrid-4-1) are different in their biologic activity.…”
Section: Hepatotoxicitymentioning
confidence: 99%
“…The gerbils treated with repeated injections of iron dextran over a period of months developed a cardiomyopathy that mimics the cardiomyopathy that develops over a period of years in patients with chronic iron overload. 8,9 Because knowledge of cardiac electrophysiology in the gerbil is limited, we also studied the rat, a species in which knowledge of cardiac electrophysiology is extensive. 25,26 Because the rat can excrete excess iron, cardiac iron deposition could not be produced in vivo in this species.…”
Section: Namentioning
confidence: 99%
“…Past efforts to examine the effects of iron on the heart have been hampered by the lack of a suitable experimental model of human iron overload; most animal species have a far greater capacity to excrete iron than humans. Recently, Carthew et al 8,9 reported that weekly subcutaneous injections of iron dextran to Mongolian gerbils reproduced critical features of the cardiomyopathy found in human iron overload, in part because the gerbil seems unable to excrete iron as effectively as other rodents. We hypothesized that abnormal excitability of iron-loaded heart cells might contribute to arrhythmias, and we examined membrane currents of single cardiomyocytes isolated from the hearts of iron-loaded gerbils.…”
mentioning
confidence: 99%